Pengaruh Kebijakan Deviden, Struktaur Modal, Set Peluang Investasi, Dan Profitabilitas Terhadap Nilai Perusahaan - Mahirun, Mahirun; Ayuningrum, Anggrainy Putri; Prasetiani, Titi Rahayu; Kushermanto, Andi (Universitas Dian Nuswantoro, 2023)
The research objective is to empirically examine the effect of dividend policy, profitability, capital structure, and investment opportunity set on firm value. The object used is the LQ45 index company on the Indonesia Stock Exchange during the period 2017-2021. The analytical tool we use is multiple linear regression using SPPS software. The results of testing 134 samples over a period of 5 years resulted in the findings of profitability with the return on equity (ROE) indicator, and the investment opportunity set with the price earning ratio (PER) indicator being able to significantly increase the company's value with the price to book value (PBV) indicator. While other findings are dividend policy with dividend payout ratio (DPR) indicator has a negative and insignificant effect on firm value (PBV). While the capital structure with the debt to equitu ratio (DER) indicator although it has a positive effect on firm value (PBV), but the results are not significant.